Uma avaliação do sistema socioeducativo cearense: olhares e narrativas sobre as trajetórias de unidades de internação de Fortaleza, Ceará - Pinheiro, Renan Santos (2022)
This dissertation presents an evaluation of the socio-educational service policy in a closed environment in the state of Ceará, based on field incursions, of an ethnographic nature, to the inpatient units of the city of Fortaleza. For this, field observations are analyzed in three socio-educational care units, which accompany the execution of definitive internment measures: the Centro Socioeducativo Dom Bosco, the Centro Socioeducativo Cardeal Aloísio Lorscheider and the Centro Socioeducativo Patativa do Assaré. I interviewed a group of people who had their lives crossed by the units surveyed: family members, graduates, professionals and human rights activists. Through in-depth interviews, field observations, analysis of documents and news in newspapers, I briefly reconstructed the trajectories of the three units, presenting the main events, phenomena and disputes that occurred over the last few years, more specifically between 2010 and 2022. As a result of the research, the following dimensions and phenomena were verified: i) reports and observations of records of numerous episodes of institutional violence against inmates by public agents, such as military police and socio-educational agents; ii) the narratives of workers that point to the experience of very hostile contexts regarding the work environment, in which feelings such as fear and anxiety are common; iii) the presence of criminal factions active in the socio-educational system and in the outskirts of the city of Fortaleza, which creates new dilemmas for socio-educational policy, such as rivalry between inmates, culminating in repeated episodes of interpersonal violence and even homicides; iv) the routine of the units surveyed in the period referring to the global pandemic of coronavirus and its impacts on internal dynamics; and v) the history of CEDECA Ceará and Ceará civil society in the social control of socio-educational policy through narrative disputes, complaints and judicial demands. After analyzing the data collected in the three units, the study argues that the socio-educational system in a closed environment was and remains an institution marked by violence and cruelty, so that it has not fulfilled its intended purpose of resocialization.